Effect of Awards and Perception Towards the Work of The Commitment of The State High School Teacher's Organizational Commitment - Oktaviano, Forman Setya; Budiono, Eko (Edukasi, 2021)
This research can find out (1) the impact of appreciation on the understanding of the work of public high school teachers, (2) the impact of rewards on organizational loyalty of public high school teachers, and (3) the impact of job understanding on organizational loyalty of public high school teachers. The research methodology used is a survey with lane analytical techniques in testing the thesis. This study used samples of about 96 state high school teachers to take simple random samples (simple random samples). This research was conducted in the North Jakarta area. Based on the details of the thesis test, the research results can be broken down as follows: (1) there is a direct positive impact of rewards on job understanding; (2) there is a direct positive impact of rewards on organizational loyalty; and (3) there is a direct impact of positive job understanding on organizational loyalty. The implementation of this research is an effort to increase the loyalty of public high school teachers, which can be implemented through increasing appreciation and understanding of work.